Effect of Ionic Surfactants on Kinetics and Mechanism of the Bi(III) Ion Electroreduction in the Mixed Aqueous–Organic Solutions of Supporting Electrolytes - Alicja Pawlak; Agnieszka Nosal-Wiercińska (Molecules)
This work presents the results of a study on the effect of ionic surfactants: cationic hexadecyltriammonium bromide (CTAB) and anionic sodium salt of sulfonic acid (1OSASS) on the Bi(III) electroreduction process in mixed aqueous–organic supporting electrolyte solutions containing methanol. This study showed that the composition of the supporting electrolyte solution, particularly the methanol and surfactant concentrations, significantly affects the mechanism and rate of the Bi(III) ion electroreduction. Analysis of the influence of the indicated factors on the mechanisms and kinetics of metal ion electroreduction can contribute not only to the optimization of industrial electrochemical processes but also to the development of innovative technological solutions, such as advanced electrochemical materials and novel sensors. In these experiments, an innovative electrode made of cyclic renewable liquid silver amalgam (R-AgLAFE) was used as a working electrode, which stands out among classic mercury electrodes (HMDE type) due to the significant reduction in mercury consumption while maintaining similar performance.